Beyond Rainmaking: Cultural Education and Collective Learning in the Brendung Ritual of Indonesian Agrarian Society - Gading Suryadmaja; Antonius Sukoco (Global Journal of Social Learning, 2026)
This study examines the Brendung ritual in Langensari Village, Pekalongan, Indonesia, as a community-based social learning system. Although Brendung is traditionally performed as a rainmaking ritual during periods of drought, its functions extend beyond ecological and spiritual purposes. Using a qualitative ethnographic approach, data were collected through participant observation, semi-structured interviews, and documentation involving ritual leaders, musicians, community elders, and youth participants. The findings show that Brendung serves as an informal learning environment where cultural knowledge, ritual competencies, social values, and local identity are transmitted across generations through participation. Collective musical practices and communal engagement facilitate experiential learning based on observation, imitation, collaboration, and direct involvement. The ritual also reproduces values of cooperation, solidarity, respect for tradition, and awareness of human–nature relationships. Furthermore, participation contributes to cultural identity formation and strengthens community resilience by sustaining social cohesion and cultural continuity. The study proposes the Brendung Social Learning Model, which explains the relationship between ritual participation, collective musical practice, experiential learning, cultural transmission, identity formation, and cultural sustainability.